An Overview of Systematic Reviews to Inform the Institutional Design of Scientific Advisory Committees. Issue 9 (8th August 2018) - Behdinan, Asha; Gunn, Elliot; Baral, Prativa; Sritharan, Lathika; Fafard, Patrick; Hoffman, Steven J.
Abstract: The current lack of synthesized evidence for informing the design of scientific advisory committees (SACs) is surprising in light of the widespread use of SACs throughout decision‐making processes. While existing research points to the importance of quality, relevance, and legitimacy for SACs' effectiveness, those planning SACs would benefit from efforts to systematically pinpoint optimal designs of these committees for maximal effectiveness. Search strategies are developed for seven electronic databases. Of the 1895 systematic reviews identified, six reviews meet the inclusion criteria: they report the results of systematic reviews that followed a clearly identified systematic methodology, examine factors related to the design of SACs, and involve processes in the natural or social sciences. These reviews collectively summarize 444 primary studies. Three of the six reviews look at the impacts of SAC size, two evaluate the influence of the committee's diversity, and half mention the importance of properly on‐boarding new members. The goal is to identify recurring themes to understand the specific institutional features that optimize the usefulness of SACs. In turn, this overview of systematic reviews aims to contribute to a growing body of literature on how SACs should be designed to maximize their effectiveness and helpfulness for decision‐making. Abstract : A breakdown of the structural aspects of scientific advisory committees (SACs) is provided and current gaps in the social science literature on their design are highlighted. The study compiles lessons that can provide guidance on the formation of SACs to ensure that these groups have a greater chance of being effective.